The influence of water and air temperature on wheelchair triathlon performance: A retrospective analysis of elite competition data - Borg, D. N.; Gibson, A.; Bach, A. J. E.; Beckman, E. M., Tweedy, S. M.; Stewart, I. B. (OSF Preprints, 2024)
Aims: Impaired thermoregulatory function is a clinical feature of many health conditions that affect triathletes using wheelchairs and consequently, individual athlete performances may fluctuate according to environmental temperature. We aimed to determine the effect of 1) water temperature on wheelchair triathlon swim time, and 2) air temperature on handcycle and wheelchair run (push) time.